10(x + 4) + 15(x + 1)
25x + 55
25x + 5
55x

10(x + 4) + 15(x + 1)
= 10x + 40 + 15x + 15
= (10x + 15x) + (40 + 15)
= 25x + 55

Expert answered|jeifunk|Points 31611|

Question

Asked 9/11/2014 7:17:43 AM

Updated 9/11/2014 7:39:25 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/11/2014 7:39:04 AM], Unconfirmed by andrewpallarca [9/11/2014 7:39:10 AM]

s

Rating

There are no new answers.

Solve the following equation. Then place the correct number in the box provided.
5x = 7.3 + 4x
User: Solve the following equation. Then place the correct number in the box provided.
4 - 7x + 10 = 15 - 6x - 8
**Weegy:** 4 - 7x + 10 = 15 - 6x - 8 -7x + 6x = 15 - 8 - 4 - 10 -x = -7 x = 7 **User:** Solve the following equation. Then place the correct number in the box provided.
3x + 1 = 2x + 12
**Weegy:** 3x + 1 = 2x + 12 3x + 1 = 12 - 2x x + 1 = 12 x = 12 - 1 x = 11 **User:** Solve the following equation. Then place the correct number in the box provided.
x + 6 - 5 = 8 - 2
**User:** the item to the trashcan. Click the trashcan to clear all your answers.
Solve the following equation. Then place the correct number in the box provided.
x + 2 = 10
(More)

Question

Not Answered

Updated 9/17/2014 8:52:43 AM

3 Answers/Comments

5x = 7.3 + 4x

5x - 4x = 7.3

x = 7.3

5x - 4x = 7.3

x = 7.3

Added 9/17/2014 8:46:20 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/17/2014 8:53:33 AM]

x + 6 - 5 = 8 - 2

x + 1 = 6

x = 6 - 1

x = 5

x + 1 = 6

x = 6 - 1

x = 5

Added 9/17/2014 8:46:49 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/17/2014 8:53:54 AM]

x + 2 = 10

x = 10 - 2

x = 8

x = 10 - 2

x = 8

Added 9/17/2014 8:47:14 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/17/2014 8:54:18 AM]

Solve the following equation. Then place the correct number in the box provided.
x + 5 = 2x
User: Solve the following equation. Then place the correct number in the box provided.
9x - 3.2 = 6.8 + 8x
**Weegy:**
9x - 3.2 = 6.8 + 8x;
9x - 8x = 6.8 + 3.2;
x = 10
**User:** Solve the following equation. Then place the correct number in the box provided.
x + 6 - 5 = 8 - 2
**Weegy:**
x + 6 - 5 = 8 - 2;
x + 1 = 6;
x = 6 - 1;
x = 5
**User:** Solve the following equation. Then place the correct number in the box provided.
3x + 1 + 5x = 7 + 15 + 7x
**Weegy:** 3x + 1 + 5x = 7 + 15 + 7x; 8x + 1 = 22 + 7x; 8x - 7x = 22 - 1; x = 21 **User:** Solve the following equation. Then place the correct number in the box provided.
8 + x = 13 + 2x
**Weegy:** 2x + x^2 = 8; x^2 + 2x - 8 = 0; (x + 4)(x - 2) = 0; x + 4 = 0; x = -4; x - 2 = 0; x = 2 Solutions are: x = -4 or x = 2 **User:** Solve the following equation. Then place the correct number in the box provided.
8 + x = 13 + 2x
(More)

Question

Updated 9/17/2014 8:48:55 AM

2 Answers/Comments

x + 5 = 2x

x - 2x = -5

-x = -5

x = 5

x - 2x = -5

-x = -5

x = 5

Added 9/17/2014 8:41:18 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/17/2014 8:49:35 AM]

8 + x = 13 + 2x

8 - 13 = 2x - x

-5 = x

x = -5

8 - 13 = 2x - x

-5 = x

x = -5

Added 9/17/2014 8:43:07 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/17/2014 8:50:19 AM]

Solve the following equation. Then place the correct number in the box provided.
2x - 20 = 32
**Weegy:** |2x - 5| = 4; -(2x - 5) = 4; -2x + 5 = 4; -2x = 4 - 5; -2x = -1; x = 1/2 - - - (2x - 5) = 4; 2x = 4 + 5; 2x = 9; x = 9/2, x = 1/2 or x = 9/2 **User:** Solve the following equation in your notebook. Then place the correct number in the box provided.
20 - 3x = 8
(More)

Question

Updated 9/24/2014 12:33:45 AM

2 Answers/Comments

2x - 20 = 32

2x = 32 + 20 = 52

x = 52/2 = 26

2x = 32 + 20 = 52

x = 52/2 = 26

Added 9/24/2014 12:33:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [9/24/2014 12:37:24 AM]

Solve the following equation. Then place the correct number in the box provided.
7 + x + 2 = 9 + 3
**Weegy:**
7 + x + 2 = 9 + 3;
x + 9 = 12;
x = 12 - 9;
x = 3
(More)

Question

Expert Answered

Updated 9/17/2014 8:55:28 AM

0 Answers/Comments

Evaluate 6^0 + 6^1 + 6^2
18
42
43 **Weegy:** Please clarify your question. You are missing some symbols **User:** Simplify the following expression.
5(2x -3) + 4( x + 1)
(More)

Question

Updated 9/10/2014 9:43:19 AM

2 Answers/Comments

6^0 + 6^1 + 6^2

= 1 + 6 + 36

= 7 + 36

= 43

= 1 + 6 + 36

= 7 + 36

= 43

Added 9/10/2014 9:42:39 AM

This answer has been confirmed as correct and helpful.

5(2x - 3) + 4(x + 1)

= 10x - 15 + 4x + 4

= 14x - 11

= 10x - 15 + 4x + 4

= 14x - 11

Added 9/10/2014 9:43:19 AM

This answer has been confirmed as correct and helpful.

32,550,256

questions answered

There are no comments.